Genetic influence of vitamin D receptor gene polymorphisms on osteoporosis risk - Banjabi, Abeer A.; Ayat B. Al-Ghafari; Taha A. Kumosani; Kurunthachalam Kannan; Salah M. Fallatah (International Journal of Health Sciences, 2020)
Objective: Osteoporosis is the most common type of bone disorder characterized by low bone mineral density (BMD). It is a multifactorial disease and caused by the interaction of environmental and genetic factors. It has been reported that mutations in the vitamin D receptor (VDR) gene highly affect the metabolism of minerals, which reduces bone density. Therefore, this study aimed to determine the association of VDR gene polymorphisms TaqI (rs731236) and ApaI (rs7975232) with osteoporosis risk in the Saudi population. Methods: This case–control study involved 73 individuals with osteoporosis and 73 healthy controls in Jeddah, KSA. DNA extracted from peripheral blood was used to determine the genotypes and allele frequencies of VDR variants by polymerase chain reaction-restriction fragment length polymorphisms. Osteoporosis was confirmed by measuring BMD using dual-energy X-ray absorptiometry. The results were interpreted using the Hardy–Weinberg equilibrium assumption with P < 0.05 considered as significant. Results: A significant increase in the genotype frequencies of the ApaI (Aa) and (aa) was observed among osteoporotic patients compared to controls (P = 0.002 and P < 0.0001, respectively). Only the homozygous (tt) genotype of TaqI was significantly higher in those with osteoporosis than in the controls (P = 0.001). The minor “a” allele of ApaI and the “t” allele of TaqI were significantly more common in the patients as compared to controls (P < 0.0001 and P = 0.01, respectively). Conclusion: VDR polymorphisms ApaI and TaqI were found to be significantly determinant risk factors for osteoporosis progression in the Saudi population.